Quando a interface é a mensagem: procedimentos técnico-estéticos como estratégias de diferenciação em portais de informação: uma análise dos portais UOL e Globo.com - Bittencourt, Daniel de Andrade (Universidade do Vale do Rio do Sinos, 2007)
This work seeks to understand the way for which the information portals create strategies to be differentiated before the hearing. Marshall McLuhan's theory of the medium is taken as center to discuss the constitution of Web's grammar of communication, what will reflect itself in the construction of the portal's interface. Silverstone is taken to argue temporalities detected in that environment, as well as Johnson's concept of Emergence assists to understand the nature of changes for which interfaces pass. Concepts of Kilpp, Bolter & Grusin and Vilches, among others, are used to map, in the layers of UOL and Globo.com's portals, the technician-aesthetic procedures that evidence the form of each portal creates its proper signification
Keywords: audiência; estratégias de diferenciação; interface; web; portais de informação; Ciências Sociais Aplicadas